Development and Quality Evaluation of Pearl Millet Based Anti-diabetic Flour - Shrma, Ankita; Choudhary, Maya (Annals of Arid Zone, 2016)
Pearl millet is produced and consumed in arid and semi-arid regions of Rajasthan as staple food grain, missi roti composite flour Indian bread is consumed by diabetics to manage the blood glucose level, however, a beneficial combination for diabetics is not known. Hence the pearl millet (PM) based anti-diabetic flour were developed. After several trails of different proportions of PM, barley (BY) and Bengal gram (BG); a proportion of 3:2 of PM and BG and 3:1:1 of PM, BG and BY were found most suitable in the preparation of roti and were acceptable by panel of judges. Recipe for roti was standardized for its carbohydrate content (40 g/serve), serving size, cooking time, cooked weight, water required for preparing the dough and acceptability on nine point hedonic scale (scores >6). Moisture, protein, fat, ash, fiber, carbohydrate and energy contents per 100 g for PM+BG, PM+BG+BY composite flour ranged from 10.79-12.10, 6.43-15.53, 2.51-3.14, 0.97-1.07, 1-2.14, 2.51-3.14, 0.97-1.07, 1-2.14, 66.20-77.12 g and 354-363 kcal, respectively. Composite flour were providing 75-85% energy from carbohydrate and were a good sources of fiber. Quality of the protein was better for composite flour (9-10.4 NDPcal%) than plain flour (1.7 NDAPcal%). Developed flour stored in 1 kg capacity flour bags at room temp for a period of three months showed an increase in free fatty acid and peroxides with storage, but did not exceed the safe limit. However, acceptability of roti from PM flour decreased significantly (P>0.05) at one month of storage, whereas roti of its blends (PM+BG and PM+BG+BY) remained acceptable up to two months of storage. Glucose tolerance test from 40 g and test recipes, i.e. plain and missi roti and kachari chutney on diabetic (n=10) and non diabetic subjects (n=10) of 30-55 years age range at 0, Â½, 1, 1Â½ and 2 hour after feeding showed lower glycaemic index (GI) values for PM+BG (54) and PM+BG+BY (74) flour than the plain PM flour (78). On the basis of the findings it can be concluded that composite flour are better for diabetics and blend of pearl millet with Bengal gram is the best. Key words: Pearl millet, Bengal gram, barley, diabetic, glycaemic index, glucose.